Pelatihan Pengembangan Produk UMKM Pada Budidaya Rumput Laut Untuk Meningkatkan Perekonomian Masyarakat Di Desa Panda Kec. Palibelo Kab. Bima - Adelia Mariam Febriana; Adinda Faudila Alhumaira; Dewi Sekar Wangi; Yunita Haryani; Putri Setia Ningrum; Aris Munandar (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
Article on the Development of Umkm Products in Seaweed Cultivation in Panda Village, Palibelo District, Bima Regency in processing seaweed into a new product innovation in the form of seaweed sticks. The aim of this service activity is to help create product innovations from local potential to help increase the income of the Panda Village community. Seaweed itself is one of the superior products of the local area which still lacks processing and knowledge of the benefits of seaweed itself. Seeing the existing opportunities, we developed seaweed such as seaweed sticks and conducted training in making attractive packaging with the aim of helping develop regional potential and increasing community creative businesses. collaborate with various parties. The method used is skills training, knowledge, coaching, mentoring, and technology diffusion, namely direct involvement of residents in the process of processing the grass until it becomes a seaweed stick product that is ready to be marketed. The impact of this development is that grass stick MSMEs will add to the long list of MSMEs in the Panda Village area.